Two 5-(thiophene-2-yl)oxazole derived "turn on" fluorescence chemosensors for detection of Ga3+ and practical applications. (17th May 2022) - Liu, Yuanying; Wang, Haitao; Guo, Xiaochuan; Xing, Yujing; Wei, Kehui; Kang, Mingyi; Yang, Xiaofeng; Pei, Meishan; Zhang, Guangyou
Abstract : Sensors L1 and L2 show highly selective responses to Ga 3+ even over Al 3+ and In 3+ with effective fluorescence enhancement. Abstract : Two (5-(thiophene-2-yl)oxazole derived chemosensors, N ′-(2-hydroxybenzylidene)-5-(thiophene-2-yl)oxazol-4-carbonylhydrazine (L1 ) and N ′-(3-ethoxy-2-hydroxybenzylidene)-5-(thiophene-2-yl)oxazol-4-carbonylhydrazine (L2 ), were designed and synthesized via a fluorescence turn-on strategy to specifically recognize Ga 3+ . Both L1 and L2 showed highly sensitive and selective fluorescence responses toward Ga 3+ in the DMSO/H2 O buffer solution and exhibited more effective anti-interference performance over other coexisting metal ions including Al 3+ and In 3+ . The limits of detection for Ga 3+ were found to be 6.23 × 10 −8 M and 1.15 × 10 −8 M with L1 and L2, respectively. Job's plots and mass spectrometry (ESI-MS) suggested a 1 : 2 complexation ratio of sensors to Ga 3+ with binding constants of 8.54 × 10 8 M 2 for L1 and 1.06 × 10 8 M 2 for L2 . The proposed interaction mechanism was further supported by density functional theory. In addition, both sensors were applied to the detection of Ga 3+ in environmental water samples.